Pengaruh pemberdayaan keluarga terhadap self-care manajamen pada pasien hipertensi: Sebuah studi literatur - Yuri Hartika Sari; Reni Zulfitri; Agrina Agrina (Holistik Jurnal Kesehatan, 2026)
Background: Hypertension is one of the noncommunicable diseases with a high prevalence in Indonesia and is a leading cause of morbidity and mortality. Patients’ poor self-care management skills and limited family support make it difficult to control blood pressure, particularly among the Malay community, which has a high-sodium diet and low physical activity levels. Family empowerment is a nursing strategy that positions the family as an active partner in the management of hypertension through education, guidance, and shared decision-making. Purpose: To identify and analyze the impact of family empowerment on self-care management in patients with hypertension based on the results of previous empirical studies. Method: A literature review was conducted by examining relevant scientific articles on family empowerment and self-care management in hypertensive patients. The literature search was performed using electronic databases such as Google Scholar, Wiley, PubMed, and ScienceDirect with the keywords “family empowerment,” “self-care management,” and “hypertension.” Inclusion criteria included articles published within the last 5–10 years, written in Indonesian or English, and available in full text. The selected articles were then systematically analyzed to identify the relationship between family empowerment and self-care management. Results: The findings indicate that family empowerment has a positive influence on improving self-care management in patients with hypertension. Family empowerment can enhance patients’ motivation, self-efficacy, and adherence to medication, healthy eating habits, physical activity, and blood pressure monitoring. Additionally, family support plays a role in creating an environment conducive to health behavior change. Conclusion: Family empowerment is an effective strategy for improving self-care management in patients with hypertension. Therefore, healthcare providers are encouraged to involve families in every nursing intervention to enhance the success of hypertension management.   Keywords: Family Empowerment; Hypertension; Self-Care Management.   Pendahuluan: Hipertensi merupakan salah satu penyakit tidak menular dengan prevalensi tinggi di Indonesia dan menjadi penyebab utama morbiditas serta mortalitas. Rendahnya kemampuan self-care management pasien dan minimnya dukungan keluarga menyebabkan tekanan darah sulit terkontrol, terutama pada komunitas Melayu yang memiliki gaya hidup tinggi garam dan aktivitas fisik rendah. Family Empowerment merupakan strategi keperawatan yang menempatkan keluarga sebagai mitra aktif dalam pengelolaan hipertensi melalui edukasi, pendampingan, dan pengambilan keputusan bersama. Tujuan: Untuk mengetahui dan menganalisis pengaruh pemberdayaan keluarga terhadap self-care management pada pasien hipertensi berdasarkan hasil penelitian empiris sebelumnya. Metode: Penelitian studi literatur dengan menelaah artikel ilmiah yang relevan terkait pemberdayaan keluarga dan self-care management pada pasien hipertensi. Pencarian literatur dilakukan melalui database elektronik, seperti Google Scholar, Wiley, PubMed, dan ScienceDirect dengan menggunakan kata kunci “family empowerment”, “self-care management”, dan “hypertension”. Kriteria inklusi meliputi artikel yang dipublikasikan dalam 5–10 tahun terakhir, berbahasa Indonesia atau Inggris, serta tersedia dalam teks lengkap. Artikel yang terpilih kemudian dianalisis secara sistematis untuk mengidentifikasi hubungan antara pemberdayaan keluarga dan self-care management. Hasil: Pemberdayaan keluarga memiliki pengaruh positif terhadap peningkatan self-care management pada pasien hipertensi. Pemberdayaan keluarga dapat meningkatkan motivasi, efikasi diri, dan kepatuhan pasien dalam menjalankan pengobatan, pola makan sehat, aktivitas fisik, serta pemantauan tekanan darah. Selain itu, dukungan keluarga juga berperan dalam menciptakan lingkungan yang kondusif bagi perubahan perilaku kesehatan. Simpulan: Pemberdayaan keluarga merupakan strategi yang efektif dalam meningkatkan self-care management pada pasien hipertensi. Oleh karena itu, tenaga kesehatan diharapkan dapat melibatkan keluarga dalam setiap intervensi keperawatan guna meningkatkan keberhasilan pengelolaan hipertensi.   Kata Kunci: Hipertensi; Pemberdayaan Keluarga; Self-Care Management.